2017
DOI: 10.1089/mab.2017.0014
|View full text |Cite
|
Sign up to set email alerts
|

ChLpMab-23: Cancer-Specific Human–Mouse Chimeric Anti-Podoplanin Antibody Exhibits Antitumor Activity via Antibody-Dependent Cellular Cytotoxicity

Abstract: Podoplanin is expressed in many cancers, including oral cancers and brain tumors. The interaction between podoplanin and its receptor C-type lectin-like receptor 2 (CLEC-2) has been reported to be involved in cancer metastasis and tumor malignancy. We previously established many monoclonal antibodies (mAbs) against human podoplanin using the cancer-specific mAb (CasMab) technology. LpMab-23 (IgG, kappa), one of the mouse anti-podoplanin mAbs, was shown to be a CasMab. However, we have not shown the usefulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…(7) We further showed that Gly54-Leu64 peptide of hPDPN is a critical epitope of LpMab-23. (15) The epitope of PMab-38 for dPDPN is similar to those of LpMab-2 and LpMab-23 for hPDPN. Therefore, this kind of epitope mapping provides important evidence for clinical application of anti-PDPN mAbs.…”
Section: Figmentioning
confidence: 83%
See 1 more Smart Citation
“…(7) We further showed that Gly54-Leu64 peptide of hPDPN is a critical epitope of LpMab-23. (15) The epitope of PMab-38 for dPDPN is similar to those of LpMab-2 and LpMab-23 for hPDPN. Therefore, this kind of epitope mapping provides important evidence for clinical application of anti-PDPN mAbs.…”
Section: Figmentioning
confidence: 83%
“…(12) In contrast, PMab-38 showed cancer specificity in immunohistochemistry using canine tissues (2) in the same pattern with anti-human PDPN (hPDPN) cancer-specific mAbs, such as LpMab-2 (7,13) and LpMab-23. (6,14,15) We previously showed that Thr55-Leu64 peptide of hPDPN, especially O-glycan attached in Thr55 and Ser56 of hPDPN, is a critical epitope of LpMab-2. (7) We further showed that Gly54-Leu64 peptide of hPDPN is a critical epitope of LpMab-23.…”
Section: Figmentioning
confidence: 99%
“…Those CasMabs against hPDPN can detect only hPDPN-expressing cancer cells, not normal cells, including lymphatic endothelial cells and pulmonary type I alveolar cells. Although LpMab-2 might bind to both a peptide and glycans of hPDPN [ 17 ], LpMab-23 could detect the conformational change of hPDPN peptides, which might be induced by cancer-specific glycans [ 38 ]. Both LpMab-2 and LpMab-23 possess high antitumor activities by those antibody-dependent cellular cytotoxicities (ADCC) [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although LpMab-2 might bind to both a peptide and glycans of hPDPN [ 17 ], LpMab-23 could detect the conformational change of hPDPN peptides, which might be induced by cancer-specific glycans [ 38 ]. Both LpMab-2 and LpMab-23 possess high antitumor activities by those antibody-dependent cellular cytotoxicities (ADCC) [ 38 , 39 ]. Furthermore, LpMab-23-recognizing cancer-type podoplanin could be a novel predictor for a poor prognosis of early stage tongue cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…When mineralized nodules contact collagen fibers around mineralized nodules, collagen mineralization is propagated from collagen, fiber to fiber [ 4 , 6 , 12 , 25 , 27 ]. Podoplanin is a sialoprotein containing sialic acid with high binding activity such as for platelet aggregation as described above [ 14 16 ]. In this study, the anti-podoplanin inhibited the mRNA and protein production of podoplanin, osteopontin, and osteocalcin in osteoblasts under the condition of mineralization (Figs.…”
Section: Discussionmentioning
confidence: 99%